Upaya Pelestarian Randai Rambun Dunia oleh Masyarakat Jorong Sungai Angek Kenagarian Simarasok - Deby Deswariani; Herlinda Mansyur (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
This study aims to describe the efforts to preserve the world's rambun randai in Jorong Sungai Angek. The type of research used in this study is qualitative research with a descriptive method. The main instrument in this study is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques are carried out by means of observation, interviews, documentation and literature studies. The types of data used are primary data and secondary data. The steps to analyze data are collecting data, describing the data and inferring the data. The results of the study show that efforts to preserve the world's rambun randai are carried out by increasing the number of perpetrators, which initially only 2 people remained, now the number of randai players has reached 12 people. Of the number of uses of the world's rambun randai, it only appears once a year at the Angek River alek activity, but now it is also displayed at weddings and outside the Jorong Sungai Angek area